Evaluation of Injuries Caused by Sharp Objects in Different Suicide Cases - Strelčenko, Jekaterina; Chmieliauskas, Sigitas; Laima, Sigitas; Vasiljevaitė, Diana; Stasiūnienė, Jurgita; Petreikis, Paulius (Acta medica Lituanica, 2026)
Background: Suicide, defined as the act of taking one’s own life, is a common cause of death worldwide, with more than 720,000 people dying by suicide each year. However, suicide by sharp objects is relatively rare, accounting for only a small percentage of all cases. In some cases, self-inflicted injuries may be mistaken for other causes, such as assault or accidental trauma. The mortality rate from self-inflicted injuries with sharp objects is low, and most such suicide attempts do not lead to death. The low fatality rate associated with self-inflicted sharp force injuries may prompt the use of an additional method, which characterizes a complex suicide. Therefore, in this article, we will analyze the injuries caused by sharp objects in different suicide cases. Materials and methods: In this retrospective study, we analyzed injuries caused by sharp objects in complex suicides with the objective to identify correlations with the suicide methods used. From 2019 to 2024, 98 nonconsecutive, impersonalized suicide autopsy cases (71 men and 27 women) involving self-inflicted cuts or stab wounds were selected from data provided by the State Forensic Medicine Service of Lithuania. All victims underwent full autopsies, including toxicological testing for alcohol and drugs. A literature search was conducted in the PubMed database by using relevant keywords. The analysis focused primarily on studies from the last 10 years but also included older studies developing strong arguments. Results: The mean age of the deceased in the study sample was 45.1 ± 17.9 years, with no difference between the sexes. In more than half of the cases (n = 52), suicides occurred while sober. Among alcohol-intoxicated individuals (n = 46), the mean blood alcohol concentration (BAC) was 1.96‰ ± 1.06. The most frequent main cause of death after unsuccessful self-inflicted injuries with sharp objects was hanging, followed by exsanguination and drug poisoning. In cases of hanging, the mean age was 45 ± 15, 60% were intoxicated (n = 32), with a mean BAC of 2.04‰ ± 1.08. A median of 13 trial cuts was found, most commonly on the forearms. When the primary cause of death was exsanguination due to cut/stab wounds, 41% were intoxicated with alcohol (mean BAC was 1.92‰ ± 0.76). In this group, 59% (n = 10) had cut neck wounds affecting major vessels, 23% (n = 4) had stabbed wounds to the chest with damage to the heart and main blood vessels, 18% had cuts to the upper limbs involving arteries. The mean age of individuals varied by injury location, notably, neck at 61 ± 20 years, chest at 39 ± 12 years, upper limbs at 71 ± 9 years. In all cases, no clothes damage was observed. A mean of 8 ± 4 (median 8) superficial neck cuts were found near the main wound in fatal neck injuries, 5 ± 2 (median 6) in the lethal chest injuries, and 6 ± 1 (median 6) in the death-causing upper limb injuries. The number of trial wounds on the neck, chest, and arms did not differ significantly (p >0.05), but was significantly higher in the hanging group (p <0.05). Concerning the third most frequent cause of death, a median of 16 trial cuts was found, of which, 42% on both forearms. There was no statistically significant difference in the mean age between cases of drugs poisoning and hanging (p >0.05), while exsanguination cases showed significant difference (p <0.05). A negative correlation was observed between the age of the entire study group and the number of trial wounds. Conclusions: Suicides by sharp objects are a relatively rare phenomenon; they most commonly involve multiple superficial trial injuries alongside a fatal stab or incised wound. Suicides with sharp objects are most common among middle-aged men, and, in more than half of the cases, the individuals were sober at the time of the event. The majority of trial cuts were observed on the upper limbs, especially in cases of hanging. In all instances, no damage to clothing was observed. Recognition of injury patterns and locations, along with the absence of defensive wounds and clothing damage, could be essential for accurate forensic interpretation, particularly in complex and ambiguous cases.